Efficacy of steroidal vs non-steroidal agents in oral lichen planus: a randomised, open-label study - Aryendra Singh; Ashutosh Rai; M. Aftab; Sachin Jain; Mamta Singh (2016)
Abstract Objective: This study compared the therapeutic efficacy of steroidal and non-steroidal agents for treating oral lichen planus. Methods: Forty patients with clinical and/or histologically proven oral lichen planus were randomly placed into four groups and treated with topical triamcinolone, oral dapsone, topical tacrolimus or topical retinoid for three months. Pre- and post-treatment symptoms and signs were scored for each patient. Results: Patients in all treatment groups showed significant clinical improvement after three months ( p < 0.05), with steroidal and non-steroidal agents having equal efficacy. Furthermore, of the non-steroidal drugs, oral dapsone had greater efficacy than topical retinoid ( p < 0.05). However, no significant differences in outcome were recorded for oral dapsone vs topical tacrolimus ( p > 0.05) and for topical retinoid vs topical tacrolimus ( p > 0.05). Conclusion: Non-steroidal drugs such as dapsone, tacrolimus and retinoid are as efficacious as steroidal drugs for treating oral lichen planus, and avoid the side effects associated with steroids.